Konstruksi Pemikiran Candah dalam Jemaat Ahmadiyah (Tinjauan Filsafat Hukum Islam)
Candah in the Ahmadiyah congregation is a very substantial matter, in which it entails the sacrifice of wealth/possession(al-tad